A Quantile Based Test of Protection for Sale Model - Susumu Imai; Hajime Katayama; Kala Krishna (Queen's University, Department of Economics, 2007)
This paper proposes a new test of the Protection for Sale (PFS) model by Grossman and Helpman (1994). Unlike existing methods in the literature, our approach does not require any data on political organizations. We formally show that the PFS model provides the following prediction: In the quantile regression of the protection measure on the inverse import penetration ratio divided by the import demand elasticity, its coefficient should be positive at the quantile close to one. We examine this prediction using the data from Gawande and Bandyopadhyay (2000). The results do not provide any evidence favoring the PFS model.
Keywords: F13; D72; F17; 330; Quantile Regression; Protection for Sale; Political Economy; Außenwirtschaftspolitik; Protektionismus; Branche; Verhalten in Organisationen; Theorie